Effects of electrolysis on magnetic abrasive finishing of AA6063-T1 tube internal surface using combination machining tool - Muhamad, Martini Ridha; Jamaludin, Mohd Fadzil; Sayuti, Mohd; Yusof, Farazila; Zou, Yan Hua (Wiley-VCH Verlag, 2018)
In this research, we studied the effects of electrolysis in the magnetic abrasive finishing of an AA6063-T1 tube internal surface. The finishing surface‘s hairline morphology was removed in a short time by physical characteristic transformation of the finishing surface in which the aluminum oxide film was formed during the electrolysis. Next, magnetic abrasive finishing was used to eliminate the oxidation layer and polish the surface to a mirror-finishing standard. The two-step process effectively improved the surface roughness in a shorter time. The morphology changes before and after the finishing process, was studied by surface roughness measurement and scanning electron microscope photographs. Notably, the pit or micro holes formation during the electrolysis on the aluminum oxide film was examined and its effect on the surface roughness was studied. The elements’ residual on the surface was investigated by X-ray photoelectron spectroscopy analyzer before and after the process to confirm the formation and removal of oxidation film on the finishing surface. The lower value for torque measurement in electrolysis combined process compared to the conventional method was due to the porous characteristic of aluminum oxide film.